THE ROLE OF DIGITAL HEALTH TECHNOLOGIES IN MANAGING CHRONIC DISEASES: A PUBLIC HEALTH PERSPECTIVE - Dr. Hiroshi Tanaka (Modern American Journals, 2025)
Chronic diseases, including diabetes, hypertension, and cardiovascular diseases, are major contributors to global morbidity and mortality. With the rise of digital health technologies, there is increasing potential for transforming how chronic diseases are managed and monitored, leading to improved patient outcomes. This paper explores the role of digital health technologies, such as telemedicine, mobile health applications (mHealth), and wearable devices, in managing chronic diseases. The advantages and challenges associated with these innovations are discussed, focusing on their impact on public health. Recent studies have shown that digital health tools can improve patient engagement, enhance self-management, and reduce healthcare costs. However, barriers such as digital literacy, data privacy concerns, and limited access in underserved populations remain obstacles to widespread adoption. This paper synthesizes recent evidence and offers recommendations for future implementation in public health strategies.
Keywords: Digital health, chronic disease management, telemedicine, mobile health apps, wearable devices, patient engagement, public health, healthcare technologies, self-management.